Compositional Analysis of Tea (Camellia sinensis) Seed Oil and Its Application - Yahaya L.E.; Adebowale K.O.; Olu-Owolabi B.I.; Menon A.R.R. (International Journal of Research in Chemistry and Environment (IJRCE), 2011)
Tea (camellia sinensis) seed oil, TSO was subjected to physical, chemical and instrumental analyses with a view for assessing its composition and technical applications. Physical and chemical properties such as color (lovibond), specific gravity, acid value, iodine index, hydroxyl value, saponification value etc., were studied. Gas chromatographic analyses of the oil indicated that TSO comprises 25% saturated fatty acids (palmitic and stearic) and 75% unsaturated fatty acids (C18:1, C18:2 and C18:3). The iodine value of TSO (74gI2/100g) suggests that it is non-drying. 1H and 13C NMR spectrometry and Infra red spectroscopy (FTIR) analyses of the oil were also carried out and these further confirm the existence of these fatty acid chains. This study therefore indicates that TSO is a promising oleochemical and can therefore be harnessed for this purpose.